Модель маршрутизації у телекомунікаційній мережі з використаннім шляхів, що перетинаються за вузлами - Єременко, О. С.; Андрушко, Д. В. (Видавництво Львівської політехніки, 2015)
Запропоновано розв’язання актуальної наукової та практичної задачі, пов’язаної з розробленням потокової моделі багатошляхової маршрутизації за шляхами, що перетинаються за вузлами, в телекомунікаційній мережі. Запропонована модель є подальшим розвитком відомої моделі багатошляхової маршрутизації на підставі введення в її структуру нелінійних обмежень, які відповідають за розрахунок шляхів, що перетинаються за вузлами. Результати моделювання підтвердили працездатність запропонованої потокової моделі багатошляхової маршрутизації за шляхами, що перетинаються за вузлами. Запропонована модель може використовуватись за умови забезпечення заданого рівня якості обслуговування, відмовостійкості та мережевої безпеки. In this article it was suggested a solution of topical scientific and practical problem associated with the development of flow-based model of multipath routing by overlapping by nodes paths within the Telecommunication Network (TCN). The model is a further development of the well known multipath routing model based on the introduction to the structure of non-linear constraints responsible for the calculation of routes that intersect at nodes. It is possible to obtain the order of multipath routing by overlapping by nodes paths in the solution of nonlinear programming problem with given objective function, linear constraints and nonlinear terms. Search for a compromise on the providing fault-tolerance and security, on the one hand, and quality of service, on the other, led to the fact that in some important cases the requirements for overlapping paths can be slightly reduced and it is allowable to use paths overlapping, for example, only by TCN nodes. In these routes not only sender and receiver are common, but some transit nodes, anyway they do not contain the shared communication links. This is relevant in the case when, for example, the place of failures is radio channel. Moreover, the operational reliability of node, which operates on the basis of modern switching equipment, can meet the availability factor 0.99999. Another example is the fact that the wireless radio channel of TCN is also a major source of compromise of data transmitted on OSI physical layer. That is exactly in such cases where the failures and/or compromise is inclined links, but not nodes of TCN, it is advisable to use overlapping by nodes paths, because it can lead to increased network performance with providing the same level of fault-tolerance or security as using the non-overlapping paths. Simulation results confirmed the efficiency of the proposed model of multipath routing with overlapping by nodes paths. Among the advantages of the proposed model of multipath routing with overlapping by nodes paths, one can distinguish the fact that with the same parameters of security and fault-tolerance can be achieved higher performance and quality of service parameters in TCN in a whole. The model can find its use at providing a required level of quality of service, fault-tolerance and network security. In addition, that kind of models can be the basis of relevant routing protocols.
Model of routing in telecommunication network with overlapping by nodes paths
Keywords: якість обслуговування; багатошляхова маршрутизація; потокова модель; маршрути; що перетинаються за вузлами; quality of service; multipath routing; flow-based model; by nodes paths